Platelet Signaling in Primary Haemostasis and Arterial Thrombus Formation: Part 1 - Scharf, Rüdiger E. (Hämostaseologie, 2018)
Platelets react immediately in response to traumatic vascular injury by adhesion, activation, aggregation and subsequent haemostatic plug formation. While this reaction pattern is essential for haemostasis, platelet responses can also cause occlusive thrombi in diseased arteries, leading to myocardial infarction or stroke. Initially, flowing platelets are captured from the circulation to vascular lesions. This step is mediated by glycoprotein (GP) Ib-IX-V interacting with immobilized von Willebrand factor (VWF) on exposed subendothelial components. Tethered platelets can now bind to collagen through GPVI and integrin α2β1. Outside-in signals from the adhesion receptors act synergistically with inside-out signals from soluble stimuli and induce platelet activation. These mediators operate through G protein–coupled receptors and reinforce adhesion and activation. Typical manifestations of activated platelets include calcium mobilization, procoagulant activity, cytoskeletal reorganization, granule secretion and aggregation. This requires activation of integrin αIIbβ3 with shifting into a high-affinity state and is indispensable to bind soluble fibrinogen, VWF and fibronectin. The multiple interactions and the impact of thrombin result in firm adhesion and recruitment of circulating platelets into growing aggregates. A fibrin meshwork supports stabilization of haemostatic thrombi and prevents detachment by the flowing blood. This two-part review provides an overview of platelet activation and signal transduction mechanisms with a focus on αIIbβ3-mediated outside-in signaling in integrin variants. In the first part, a three-stage model of platelet recruitment and activation in vivo is presented. Along with that, platelet responses upon exposure to thrombogenic surfaces followed by platelet-to-platelet interactions and formation of haemostatic thrombi are discussed. Moreover, several determinants involved in pathological thrombosis will be reviewed.
Keywords: platelet adhesion; activation; aggregation; thrombus formation; integrin αIIbβ3